2009
DOI: 10.1111/j.1365-2699.2009.02104.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and phylogeographic analysis of Pinus leiophylla: a post‐glacial range expansion

Abstract: Aim Mexico is a centre of diversity for species of the genus Pinus, most of which have restricted geographical distributions. An exception is Pinus leiophylla Schiede and Deppe, which is widely distributed throughout most of Mexico's mountainous regions. We attempt to reconstruct the phylogeographic history of this species, in order to determine if its current broad distribution is associated with major events of environmental change that occurred during the Quaternary.Location Coniferous forests in Sierra Mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 82 publications
2
14
0
Order By: Relevance
“…This inference was broadly congruent with diversification patterns seen in several Middle American highland pitvipers (Castoe et al. , 2009) and other montane taxa (pines: Moreno‐Letelier & Piñero, 2009; Rodríguez‐Banderas et al. , 2009; insects: Masta, 2000; Smith & Farrell, 2005; Anducho‐Reyes et al.…”
Section: Discussionsupporting
confidence: 80%
“…This inference was broadly congruent with diversification patterns seen in several Middle American highland pitvipers (Castoe et al. , 2009) and other montane taxa (pines: Moreno‐Letelier & Piñero, 2009; Rodríguez‐Banderas et al. , 2009; insects: Masta, 2000; Smith & Farrell, 2005; Anducho‐Reyes et al.…”
Section: Discussionsupporting
confidence: 80%
“…The prediction of 1961-1990 distribution in general is in agreement of maps developed by Perry (1991), Farjon and Styles (1997), Rodríguez-Banderas et al (2009) and Rehfeldt et al (2009). The area where the climate is predicted to be suitable for Pinus leiophylla is greater than the actual distribution.…”
Section: Discussionsupporting
confidence: 70%
“…(Vendramin et al, 1996), the most commonly reported primers used in Pinaceae. Common foci of studies within Pinaceae include understanding the effects of Quaternary glaciation on species range distributions (e.g., Gugerli et al, 2001; Gómez et al, 2005; Bucci et al, 2007; Rodríguez‐Banderas et al, 2009; Godbout et al, 2010), characterizing genetic structure (e.g., Vendramin et al, 1999; Dyer and Sork, 2001; Viard et al, 2001; Nasri et al, 2008; Scalfi et al, 2009; Wang et al, 2013), testing for hybridization (e.g., Fady et al, 2003; Epperson et al, 2009), paternity analysis (e.g., Lambeth et al, 2001), and testing taxonomic hypotheses (e.g., Clark et al, 2000; Ledig et al, 2004; Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%